Maternal blood proteomics during relapse of early preeclampsia - M. G. Nikolaeva; V. Yu. Terekhina; A. P. Momot (IRBIS LLC, 2024)
Aim: to study the contribution of maternal blood endothelial proteins to developing relapse of early preeclampsia (ePE).Materials and Methods. A proteomic analysis of the peripheral blood of 137 pregnant women was performed. Clinically, three groups were identified at the end of pregnancy: control (n = 40), patients with favorable course of the current and previous pregnancy; comparison group (n = 59) - patients with a history of еPE episode, but favorable course of ongoing pregnancy, and main group (n = 38) - patients with еPE relapse. Biologically active substances evidencing about impaired endothelial function were subject to dynamic monitoring (11-13, 19-21 and 27-28 weeks): activity of endothelin-1 (ET-1) and metalloproteinase ADAMTS-13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13), von Willebrand factor (vWF) level and homocysteine (HC) concentration. The ADAMTS-13/vWF ratio was evaluated separately.Results. For patients with recurrent еPE, a significant increase in ET-1 is characteristic at all stages of gestation: 0.92; 1.07 and 1.36 pmol/ml vs. 0.29; 0.33 and 0.29 pmol/ml in the control group (p < 0.0001 at all points). Regardless of pregnancy outcome, increasing gestational age was paralleled with elevating vWF level, however, upon еPE relapse, this parameter (Me = 343 IU) is significantly higher (p < 0.0001) than in control group (Me = 260 IU). In all groups, there was a significant decrease in ADAMTS-13 activity, whereas in main group ADAMTS-13 activity at first time point was minimal - 63.4 % (p = 0.0007 relative to control group). With regard to ADAMTS-13/vWF axis in relapsed еPE, significant differences were found compared with control group both at 11-13 weeks (0.32 vs. 0.52; p < 0.0001) and at 27-28 weeks (0.15 vs. 0.22; p < 0.0001) pregnancy. The HC concentration declines with gestational age, but at first time point patients from main group had it (Me = 8.0 µmol/L) at significantly higher level than in control group (Me = 5.9 µmol/L; p < 0.00010).Conclusion. At gestational age of 11-13 weeks, all analyzed biomarkers contribute to developing еPE relapse accounting for an overall impact of 62.3 % of developing ePE risk. During pregnancy at 19-21 weeks, an imbalance in the ADAMTS-13/vWF along with elevated ET-1 level determine the risk of disease relapse in 65.6 % of cases. It was found that at a gestational age of 27-28 weeks, the associated shift in ET-1, vWF and ADAMTS-13 magnitude accounts for 67.9 % of risk for disease relapse.